A literature review on BIM for cities Distributed Renewable and Interactive Energy Systems. Issue 2 (4th May 2021) - Abanda, F.H.; Sibilla, M; Garstecki, P; Anteneh, B.M.
ABSTRACT: The havoc caused by COVID-19 has further strengthen the case for greening cities and ensuring a quicker economic recovery much desired by various governments. To this end, the appetite for Distributed Renewable and Interactive Energy Systems (DRIES) as a preferred option to retrofit cities has grown amongst policy makers. However, DRIE sources are complex and disparate presenting challenges integrating into a unified system for urban retrofitting. Yet, integrating Building Information Modelling (BIM) and DRIES provide possibilities of effective assessment. Research of BIM applications at a city level is still very sketchy talk less in the domain of DRIES. This study investigates the opportunities and barriers of the application of BIM for the performance assessment of DRIES in the context of the transforming our environments into lowcarbon cities. A systematic literature review and case study review were used to achieve the aim of this study.